Economic Evaluation of Service Budget Performance in the Education Sector - Kalis Endah Wahyuni; R. Luki Karunia Karunia; Neneng Sri Rahayu (International Journal of Economics Development Research (IJEDR), 2025)
This research aims to assess budget performance at the Bekasi District Education Office for the 2020-2023 Fiscal Year period. The method used is descriptive qualitative to produce a budget performance assessment. Data collection was carried out through interviews and document review. The results of this research show the budget performance of the District Education Office. Bekasi, viewed from an economic perspective in 2020-2023, experiences fluctuations every year and is categorized as economical because the economic ratio level is between 90%-100%. For the level of efficiency in the 2020-2023 budget revenue, it is categorized as less efficient because the efficiency ratio is more than 90%. Then the level of effectiveness experienced a decrease in effectiveness from 2020-2023 but was still categorized as effective because the level of effectiveness ratio was between 90% - 100%. Therefore, the Bekasi District Education Office needs to prioritize the preparation of more efficient budget planning based on the Value for money concept. namely budget effectiveness, budget efficiency, economics, and budget.